Bipolar‐associated miR‐499‐5p controls neuroplasticity by downregulating the Cav1.2 subunit CACNB2. (15th August 2022) - Martins, Helena C; Gilardi, Carlotta; Sungur, A Özge; Winterer, Jochen; Pelzl, Michael A; Bicker, Silvia; Gross, Fridolin; Kisko, Theresa M; Malikowska‐Racia, Natalia; Braun, Moria D; Brosch, Katharina; Nenadic, Igor; et al.
Abstract: Bipolar disorder (BD) is a chronic mood disorder characterized by manic and depressive episodes. Dysregulation of neuroplasticity and calcium homeostasis are frequently observed in BD patients, but the underlying molecular mechanisms are largely unknown. Here, we show that miR‐499‐5p regulates dendritogenesis and cognitive function by downregulating the BD risk gene CACNB2. miR‐499‐5p expression is increased in peripheral blood of BD patients, as well as in the hippocampus of rats which underwent juvenile social isolation. In rat hippocampal neurons, miR‐499‐5p impairs dendritogenesis and reduces surface expression and activity of the L‐type calcium channel Cav1.2. We further identified CACNB2, which encodes a regulatory β‐subunit of Cav1.2, as a direct functional target of miR‐499‐5p in neurons. miR‐499‐5p overexpression in the hippocampus in vivo induces short‐term memory impairments selectively in rats haploinsufficient for the Cav1.2 pore forming subunit Cacna1c. In humans, miR‐499‐5p expression is negatively associated with gray matter volumes of the left superior temporal gyrus, a region implicated in auditory and emotional processing. We propose that stress‐induced miR‐499‐5p overexpression contributes to dendritic impairments, deregulated calcium homeostasis, and neurocognitive dysfunction in BD. Synopsis: Stress‐mediated upregulation of bipolar‐disorder‐associated miR‐499‐5p in rat hippocampal neurons leads to impaired surface expression of L‐type calcium channels, defective neuroplasticity, and short‐term memory impairments. miR‐499‐5p inhibits rat hippocampal neuron dendritogenesis by downregulating the expression of the psychiatric risk gene and L‐type calcium channel subunit Cacnb2. miR‐499‐5p impairs short‐term memory in rats and is negatively associated with human gray matter volume in the superior temporal gyrus. miR‐499‐5p is induced by early life adversity in rats and humans and elevated in peripheral blood of bipolar disorder patients. Abstract : Stress‐mediated upregulation of bipolar‐disorder‐associated miR‐499‐5p in rat hippocampal neurons leads to impaired surface expression of L‐type calcium channels, defective neuroplasticity, and short‐term memory impairments.